ANALGESIC ACTIVITY, PHYTOCHEMICAL PROFILING AND TOXICITY ASSESSMENT OF ETHANOL EXTRACT FROM OCIMUM GRATISSIMUM LEAVES CULTIVATED IN JOS, NIGERIA - Achuenu, Chukuka; Tanko, Simon; Nworie, Miracle Oluebube; Edah, Alexander Oba; Adelakun, Esther A. (FUDMA Journal of Sciences, 2026)
Pain is an excruciating and discomforting challenge to humans. The search for safer, cost-effective, plant-based analgesic agents from locally cultivated sources has sparked interest in medicinal chemistry. Ocimum gratissimum is a widely consumed plant in Africa for its medicinal properties. This study explored the analgesic potential, phytochemical composition, acute toxicity, and FTIR spectral characteristics of the ethanolic extract of the plant. Analgesic activity was assessed using the acetic acid-induced writhing assay in albino rats. The number of writhes was counted at 5-minute intervals for a total observation period of 40 minutes following intraperitoneal administration of acetic acid, and cumulative writhing counts were used for analysis. The result revealed a dose-dependent inhibition of writhes, with 62.27 mg/kg producing 58.46% inhibition compared to the negative control, which was comparable to the standard drug diclofenac potassium (10 mg/kg; 52.31%). Lower doses (24.44 mg/kg and 43.8 mg/kg) produced minimal inhibition (4.62 % and 4.49 %, respectively) and differences were not statistically significant (p > 0.05). The doses used in this study were selected based on preliminary experimental considerations.